Static Behavior of Steel Frame Bridge (Case Study of Citanduy Bridge, Tasikmalaya Regency) - Nurrochmat, Cahyadi; Soelarso, Soelarso; Darwis, Zulmahdi (JURUSAN TEKNIK SIPIL, 2023)
The bridge is a road-complementary structure that functions to connect two ends of the road crossed by rivers, canals, valleys, seas, highways, and railroads. A truss bridge is a bridge structure made by combining steel elements according to design criteria and binding technical aspects. Citanduy Bridge is located in Ancol Village, Cineam District, Tasikmalaya Regency, West Java. This bridge has been operated, and to determine the capacity of the bridge, the bridge will be tested for loading. Citanduy Bridge will be tested for loads using two types of loading tests: static loading tests and dynamic loading tests. A static loading test is a loading test on the bridge in which the load used in a stationary condition is placed in the middle of the bridge span based on SNI 1725:2016. The load of the trucks used in this study was 35 tons, and the number of trucks was 6. Structural analysis in this study was carried out using the evaluation version of the SAP 2000 program. Based on RSNI T-03-2005, the allowable deflection on the Citanduy bridge is 62.5 mm. Based on the results of the study, the maximum deflection value obtained from the static load test was 42 mm on a span of 25 m when combined 4, while the maximum deflection value from the results of the structural analysis was 33.7 mm on a span of 25 m when combined 4. Based on the comparison of the maximum deflection with the allowable deflection, the Citanduy bridge can be categorized as passing the static load test.